Determinants Of Student Smoking Behavior In Jambi City - Shini Justisia Ryantri; M.Ridwan; Puspita Sari (Sean Institute, 2024)
Background: Smoking continues to be one of the major health concerns. This behavior has the potential to endanger the health of the entire world and can result in death for humans. When compared to other educational categories, secondary schools (SMA/SMK) have the highest percentage of daily smokers. This study aims to determine the factors associated with adolescent smoking behavior in Jambi City State Vocational High Schools in 2023. Methods: This study is a type of quantitative method research with a cross sectional research design. The population in this study was 4,314 respondents with a research sample of 255 respondents. The sample in this study was selected through the Quota Sampling Technique. The analysis was carried out using Univariate analysis and Bivariate analysis using the chi square test. Results: There is a relationship between knowledge (p=0.047), attitude (p=0.000), cigarette affordability (p=0.000), family attention (p=0.000), peer influence (p=0.000) with adolescent smoking behavior. Conclusion: Factors associated with adolescent smoking behavior at SMK Negeri Jambi City are knowledge factors, attitudes, cigarette affordability, family attention and peer support.